Preserving fuzzy subgroups and indistinguishability operators - Bejines-López, Carlos; Chasco Ugarte, María Jesús; Elorza, Jorge; Recasens, Jordi (Elsevier, 2018)
In this paper we study the class of all fuzzy subgroups defined with respect to a given t-norm on a fixed group. We find necessary and sufficient conditions over two t-norms to guarantee that the class of all fuzzy subgroups induced by the first t-norm is contained in the class of all fuzzy subgroups with respect to by the second one. We characterize the functions that transform fuzzy subgroups into fuzzy subgroups. The close relationship between indistinguishability operators and fuzzy subgroups allows us to obtain similar results for some classes of indistinguishability operators.
Keywords: Matemáticas difusas; Fuzzy sets; Groups